A simulation study of the effect of equivalent series resistance (ESR) in DC-DC converter - Normaliza, Osman (2016)
DC-DC Converters is an electronic circuit which converts a source of direct current from one voltage level to another. Modelling of DC-DC converter with capacitor Equivalent Series Resistance (ESR) are considered in this project. ESR or parasitic is non-ideal parameter used in the design circuit. Non idealities or parasitics of practical devices and components affect some performance parameter in dc-dc converters. There are three converters studied in this project which are buck converter, boost converter and flyback converter. The operation of the converter is in the continuous conduction mode (CCM) is assumed. The simulation of the converter is carried out using the Matlab Simulink. The analysis of converters has been performed under idea switch, diode and passive component assumptions. In this project, the ESR value (rC) are 1.2Ω, 0.14 Ω and 0.014 Ω used. The effects of ESR on output voltage ripple and efficiency of converters.